Technology-based entrepreneurship in South Brazil - Siluk, Julio Cezar Mairesse; Garlet, Taís Bisognin; Marcuzzo, Rafael; Michelin, Cláudia de Freitas; Minello, Italo Fernando (Revista de Administração da UFSM, 2018)
This paper analyzes the current scenario of technology-based incubators (TBIs) in South Brazil from a socioeconomic and intellectual perspective, through correlations with higher education institutes with stricto sensu graduate programs, intellectual property rights, investments in science and technology, Gross Domestic Product (GDP) and Human Development Index (HDI). The study focused on the Brazilian South region, since it presents some of the best social indicators in the country. Based on correlation analysis, it was possible to investigate an outstanding scenario in developed nations, which involves technology-based entrepreneurship. The results show that: (1) the presence of TBIs is strongly related to the existence of higher education institutes with stricto sensu graduate programs; (2) the existence of TBIs is highly associated with high levels of intellectual production; (3) the states that receive more investment in science and technology are positively correlated with TBIs; (4) the existence of TBIs presents a negligible correlation with the GDP; (5) the existence of TBIs shows a weak correlation with the HDI. Thus, this study allowed the investigation of the South Brazilian scenario related to the implementation and operation of TBIs.